MIDDLE CARNIAN (LATE TRIASSIC) NASSELLARIA (RADIOLARIA) OF KÖSEYAHYA NAPPE FROM EASTERN TAURIDES, EASTERN TURKEY (Rivista italiana di Paleontologia e Stratigrafia, 2007)
Abundant, very diverse, and well-preserved Nassellarian fauna has been obtained from cherty/clayey limestone levels at the basal part of the Köseyahya nappe east of the town of Elbistan, Eastern Taurides. A comparison with the radiolarian faunas of Austria, Japan and Turkey allows us to assign a middle Carnian age to this radiolarian fauna from the Elbistan region. This fauna contains Nassellaria that are typical for this time interval. Moreover, it contains Tetraporobrachia haeckeli Kozur & Mostler which is an index fossil that gives the name to the zone established by Kozur & Mostler. As a result of the taxonomic study of the Nassellarian fauna, thirty-nine taxa among which nine new species (Goestlingella tueysuezi, Haeckelicyrtium planum, Hinedorcus koeseyahyaensis, Katroma ? ornata, K. ? proba, K. ? tunoglui, Syringocapsa firma, S. nuda, Sanfilippoella carterae) and twelve taxa remained in open nomenclature are described and figured in this study.